Multicopy derivative of pock-forming plasmid pSA1 in Streptomyces azureus. - Miyoshi, Y K (1986)
Streptomyces azureus carried one copy or less of plasmid pSA1, which elicited pocks at 0.1 to 1.0%. Strain PK100 was isolated from the wild-type strain after UV irradiation. PK100 carried approximately 20 to 30 copies of pSA1.1, a derivative of pSA1. Plasmid pSA1.1 elicited pocks at 100% and inhibited spore and thiostrepton production.